INTERNAL AUDIT PRACTICES AND ORGANIZATION EFFECTIVENESS: INSIGHTS FROM SMES IN KWARA STATE - Saheed Lawal; Abdulkadri Toyin Alabi (Malete Journal of Accounting and Finance)
The tenacious cases of anomalies in corporate organizations, producing at higher cost with consequently lower profit margin especially among small and medium-sized enterprises (SMEs) have raised several questions on the presence of internal audit unit. The study hence investigated how internal audit practice affects the effectiveness of SMEs in Kwara State by assessing how much remuneration and information technology expertise of internal auditors’ impact on efficiency. This research uses a survey research methodology. The heads of internal audit units and senior audit staff of the manufacturing companies within SMEs in Kwara State make up the study's target respondents (920). As of 31st January 2022, the Kwara State Internal Revenue Service (KWIRS) had four hundred and fifty (460) registered SMEs in the manufacturing/agro-allied sector. The statistical procedure developed by Yamane (1967) was used to determine the study's sample size of (279) respondents. To analyse the data, partial least square structural equation modeling (PLS-SEM) was used as an estimation approach. The outcome shows that the remuneration for internal auditors has a favourable and significant impact on the organizational effectiveness of SMEs in Kwara State. Internal auditor use of information technology, however, has a negligible and detrimental impact on the organizational performance of SMEs in Kwara State. To support internal auditors, discourage financial and material irregularities, and ultimately increase organizational performance, this research advises management of SMEs to implement both intrinsic and extrinsic forms of compensation to promote organization effectiveness.